ONE DRUG TO FIX IT ALL? THE ROLE OF TIRZEPATIDE IN TREATING COMPONENTS OF METABOLIC SYNDROME - Sylwia Tomasiczek; Weronika Tomasiczek; Dominika Kondyjowska; Zuzanna Sawiec; Natalia Bukała; Dorota Maria Komuńska; Ewa Antonowicz; Marta Rogozińska (International Journal of Innovative Technologies in Social Science, 2025)
Metabolic syndrome is a growing global health concern, driven largely by lifestyle-related factors such as poor diet, physical inactivity, and obesity. It is defined as a cluster of risk factors - including abdominal obesity, insulin resistance, hypertension, and dyslipidemia - that significantly increase the risk of developing cardiovascular disease, stroke, and type 2 diabetes. With its prevalence rising worldwide and substantial impact on morbidity and mortality, there is an urgent need for effective, multifactorial treatment strategies. Tirzepatide, a dual GIP and GLP-1 receptor agonist, has recently emerged as a promising therapeutic agent. The aim of this article is to review the current state of knowledge regarding tirzepatide’s potential in addressing key components of metabolic syndrome. Evidence from the SURPASS clinical program and the SURMOUNT-1 trial demonstrates tirzepatide’s robust effects on several metabolic parameters. It has been shown to significantly reduce HbA1c levels, promote substantial and dose-dependent weight loss, improve lipid profiles, and lower blood pressure. Notably, in a post hoc analysis of the SURPASS trials, tirzepatide led to normalization of blood glucose in a large proportion of patients and reduced the prevalence of individuals meeting the criteria for metabolic syndrome. Although metabolic syndrome was not a primary endpoint in these studies, the improvements seen across its components support tirzepatide’s potential as a comprehensive treatment. These findings suggest that tirzepatide may represent a significant advancement in the management of metabolic syndrome and offer new hope for patients burdened by multiple cardiometabolic risk factors.